Assessment of the Contributions of Different Teaching Methods to Students’ Mathematics Achievement - Omole, Olutayo Toyin; Oladele, Babatunde Kasim; Ligali, Omotayo Kabiru (Universitas Negeri Semarang, 2025)
Students’ level of learning and knowledge of mathematics has been a great concern in recent times in secondary school education. This study, therefore, investigated how the teachers’ teaching approaches correlate and contribute to junior secondary school students’ mathematics achievement in Lagos State, Nigeria. The study adopted a correlational research design. The study adopted a stratified sampling technique to select 30 junior secondary schools from the six existing educational districts, and a simple random technique was used to sample 900 students from the selected schools. Data was collected using the Teacher Teaching Methods Questionnaire (r = 0.76) and the Mathematics Achievement Test (r = 0.71). Data analysis was done using multiple regression with a significance level of less than 0.05. Combining all teachers' teaching methods (demonstration, group discussion/cooperative learning, lecture, discovery, and project) resulted in a multiple correlation coefficient (R) of 0.237. The combination of independent variables explained the variance in the dependent variable, as indicated by the adjusted R2 of 0.051. Among the teaching methods considered, the group discussion/cooperative learning method (β = 0.219, t = 5.217) and the lecture method (β = 0.094, t = 2.082) both contributed positively and significantly to students' mathematics achievement. It is therefore important for mathematics teachers to identify and adopt the best methods to teach the subject.